Protective Effect of Qiliqiangxin against Doxorubicin-Induced Cardiomyopathy by Suppressing Excessive Autophagy and Apoptosis - Yating Qin; Chao Lv; Xinxin Zhang; Weibin Ruan; Xiangyu Xu; Chen Chen; Xiaoning Wan; Xinyun Ji; Juan Zhou; Li Lu; Xiaomei Guo (Cardiovascular Therapeutics)
Background. Doxorubicin (DOX) is one of the most potent and widely prescribed antitumor agents; however, its clinical use is limited by cardiac side effects. In this study, we aimed to clarify the protective effects of Qiliqiangxin (QL), a traditional Chinese medicine formulation, on DOX-induced cardiotoxicity and to explore the underlying mechanisms in a rat model. Methods. Male Sprague-Dawley rats were randomly assigned to three groups with different interventions (control, DOX, and DOX plus QL) for 31 days. Cardiac function was monitored. The levels of oxidative stress in plasm were detected, the activities of autophagy and apoptosis in rat hearts were determined, and then, the related PI3K/AKT/mTOR signal pathway regulating apoptosis and autophagy was investigated. Results. QL improved cardiac dysfunction and decreased the increased level of cardiac enzymes in plasm caused by DOX. Moreover, DOX exposure resulted in oxidative stress enhancement, which was suppressed by QL treatment. Then, we discovered that DOX intervention caused the apoptosis of cardiomyocytes by activating the mitochondrial-dependent apoptotic pathway which was strongly inhibited by QL treatment. Furthermore, there was a significant increase in autophagic activities in the DOX-stimulated myocardium. Administration of QL substantially inhibited the enhanced autophagic activities, which might be attributed to the activation of PI3K/AKT/mTOR cascade, followed by suppression of ULK1 activity. Conclusions. QL exhibited protective roles against DOX-induced cardiotoxicity possibly via mediating the PI3K/AKT/mTOR pathway, leading to inhibition of autophagy and subsequent apoptosis activities.